Relationship between prenatal ultrasound signs and genetic abnormalities for fetal malformations of cortical development - Chen, JunYa; Zhu, Rong; Pan, Hong; Ma, YiNan; Zhu, Ying; Liu, LiLi; Hou, XinLin; Haratz, Karina Krajden (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
To explore the relationship between ultrasound signs of suspected fetal malformation of cortical development (MCD) and genetic MCD.The retrospective study involved fetuses with one of the following 10 neurosonography (NSG) signs: (A) abnormal development of the Sylvian fissure; (B) delayed achievement of cortical milestones; (C) premature or aberrant appearance of sulcation; (D) irregular border of the ventricular wall or irregular shape of the ventricle; (E) abnormal shape or orientation of the sulci; (F) hemispheric asymmetry; (G) non-continuous cerebral cortex; (H) intraparenchymal echogenic nodules; (I) persistent ganglionic eminence (GE) or GE cavitation; (J) abnormal cortical lamination.95 fetuses were included in the study. Chromosomal microarray (CMA) combined with exome sequencing (ES) was available in 40 fetuses, CMA was abnormal in nine and ES in 22. Sign C (7/7, 100%), sign H (2/2, 100%), sign A (18/19, 94.7%), and sign B (12/13, 92.3%) were the signs leading to the highest probability of genetic MCD. The incidence of genetic MCD for sign E, sign I, and sign D was 66.7–73.7%. Only one or none of the fetuses with sign J, sign F, or sign G underwent CMA+ES. The signs in the fetuses with FGFR3, CCND2, FLNA, or TSC2 mutations had the expected features. The other fetuses with different gene mutations showed several non-specific NSG signs.Several reliable signs for genetic MCD can be detected by NSG, and the probability varies with different signs. Most signs are not associated with a specific gene. Therefore, CMA combined with ES is preferred.
Keywords: malformations of cortical development; neurosonography; chromosomal microarray; exome sequencing; prenatal ultrasound